Belief elicitation study: Identifying salient beliefs of patients towards the use of mHealth - Christine Hennings; Cornelius Herstatt (Hamburg University of Technology (TUHH), Institute for Technology and Innovation Management (TIM), 2019)
Mobile health (mHealth) with its unique attributes (e.g. instant connectivity, convenience, personalization) is largely considered as a new healthcare paradigm transforming health services around the world. mHealth has also gained popularity in research, especially in the field of technology adoption. According to the Theory of Planned Behavior (TPB), a widely used and well established theory to explain behavior, salient beliefs are considered to be the dominant determinants of a person's intentions and actions. In the context of technology adoption identifiying salient beliefs is essential when thinking of effective intervention strategies and marketing strategies by e.g. public health policers and app producers. This study is from qualitative nature and contains a German sample, aiming to answer the following research question: What are the salient beliefs patients with chronic conditions have towards the use of medical apps (mHealth)? The results show behavioral, normative and control beliefs of patients. Study participants in particular value the high comfort, a good, mainly administrative, support in daily disease handling and a feeling of increased control over the disease caused by using medical apps. The most frequent negative beliefs were insecurity about data privacy issues, a feeling of becoming dependent on the app and the fear of data loss in case of a lost or broken smartphone. In regard to normative beliefs patients see the physician as an important individual to approve or disapprove their use of medical apps. Noteably in this case is, that physicians were the most frequent mentioned group for positive normative beliefs as well as for negative normative beliefs. In regard to control beliefs respondents perceived that among the most frequent facilitators that would allow the use of mHealth apps were individual requests for a specific app feature, a high usability/ease of use of the app and device compatibility of the app with other medical devices. Salient beliefs about barriers that would allow the use of mHealth apps were a low quality of an app, the absence of a suitable smartphone and a high complexity of the app. The results are potentially beneficial for app producers to gain insights for their marketing initiatives but also for public health policy.
Keywords: 330; mHealth; Theory Planned Behavior; Belief Elicitation Study